Meaningful Engagement for Happiness, Well-being, and Prosperity: Nepal in the Asia-Pacific Context - Bomjan, Mahendra Kumar (Janajyoti Journal, 2025)
This paper explores the idea of meaningful engagement and how it might advance happiness, well-being, and prosperity in the Asia-Pacific area with an emphasis on Nepal. The Asia-Pacific area is distinguished by its varied cultures, socio-economic conditions, and developmental disparities, all of which have distinct effects on prosperity and well-being. Nepal is a case study for comprehending the transformational effect of meaningful interaction because of its distinct socio-cultural setting and developmental constraints. This study investigates the ways in which social cohesiveness, long-term prosperity, and general well-being are influenced by active engagement at the individual, institutional, and community levels. The study examines examples from Nepal and other Asia-Pacific nations and stresses the importance of cultural values, social inclusiveness, education, and legislative actions in promoting meaningful involvement. It concludes by offering recommendations for increasing participation to raise living standards and promote sustainable development in the area.